Comparison of the effectiveness and safety of vaginal and sublingual low-dose misoprostol versus vaginal dinoprostone for labor ınduction: A retrospective cohort study - Elmin Eminov; Ayşe Eminov (PLoS ONE, 2025)
Background Labor induction is one of the most common obstetric interventions, yet the optimal pharmacological agent and route of administration remain subjects of ongoing debate. Prostaglandin analogs such as misoprostol and dinoprostone are widely used for cervical ripening and induction; however, evidence comparing their effectiveness and safety across different routes is still limited. Aim The primary purpose of the study is to evaluate the efficacy and safety of vaginal and sublingual misoprostol and vaginal dinoprostone pessary in labor induction. Materials and Methods Patients were divided into three groups based on the labor induction methods used. The first group included patients who received 25 µg vaginal misoprostol for labor induction, the second group included patients who received 25 µg sublingual misoprostol, and the third group included patients who received vaginal dinoprostone pessary. The primary outcome of the study was to evaluate vaginal delivery rates and time from induction to delivery of the fetus. The secondary outcomes of the study were to evaluate cesarean delivery rates, indications for cesarean delivery, first- and fifth-minute Apgar scores, birth weight, gender, amniotic fluid meconium contamination, and admission rates to the neonatal intensive care unit (NICU). The study data were collected from the hospital’s automation system and archives. All patients’ demographic and obstetric characteristics and maternal and fetal outcomes were recorded in a spreadsheet document (Microsoft Excel™), and statistical analyses were performed using the SPSS 28.0 program. Results Vaginal delivery rates were higher in the group where vaginal (86,5%) and sublingual misoprostol (85,3%) were applied, and cesarean delivery rates were higher in the group where vaginal dinoprostone pessary (31,6%) was applied (p = 0.000). When the groups were compared according to the duration of labor, no difference was found in the vaginal (523.86 ± 405,92) and sublingual misoprostol (560.15 ± 438,00) groups, while the duration of labor was significantly higher in the dinoprostone pessary group (857.37 ± 558,36) (p = 0.000). Hyperstimulation (6.8%) (p = 0.007) and admission rates to the neonatal intensive care unit (9.1%) (p = 0.004) were higher in the dinoprostone group, and this difference was statistically significant. Conclusion According to the results of the study, low-dose vaginal or sublingual misoprostol was found to be more effective and safer than vaginal dinoprostone pessary in labor induction.